Água residuária de suínos em um sistema agroflorestal: atributos químicos e translocação de nutrientes no solo - Bernardes, Rafaella Ferreira Batista (2017)
The objective of this work was to compare soil chemical attributes under two cropping arrangements in single and double lines of Corymbia citriodora at 0 - 20 cm depth, as well as to evaluate the variation in soil chemical parameters up to the depth of 60 cm, under different swine wastewater (SW) rates, in a silvipastoral system with Corymbia citriodora planting arrangement performed in double lines. Two experiments were implemented, at the Bonsucesso farm, in the municipality of Uberlândia, MG, the first with citriodora in simple lines, with five plants per plot, spacing two meters between plants and 15 meters between rows. The second experiment was with citriodora in double lines, with two meters between plants in the line, three meters between lines in the plot and 15 meters between the double lines of citriodora. The statistical design was in randomized blocks. The treatments used were five rates of SW (0; 200; 400; 600 and 800 m3 ha-1) with five replicates. The application of SW rates were divided in the dry season, in the months of June, July and August. In order to compare soil chemical attributes among planting arrangements, soil samples were collected at depths of 0 - 20 cm depth. A joint analysis of the data was performed, comparing the soil chemical analysis. Planting on double lines of citriodora, provided higher levels of nutrients in the soil. The application of swine wastewater raised the levels of magnesium, potassium and heavy metals such as copper and zinc. No increase in soil pH was observed with the application of SW. The dose of 200 m ha , provided adequate contents for most of the nutrients present in the soil. For the evaluation of variations of soil chemical attributes in the Corymbia citriodora planting arrangement in double rows, three samples per plot were collected at depths of 0 - 20, 20 - 40 and 40 - 60 cm. A randomized complete block design 3 -1 was used in subdivided plot arrangement. The dose of 200 m ha swine wastewater provided adequate soil contents for nutrients K, Na, Cu and Zn. There was leaching to the depth of 60 cm of K, Na, Cu and Zn. The Mg contents reduced in the soil with the application of swine waste water. SW did not change soil pH and Ca content.